2019
DOI: 10.1016/j.neuropsychologia.2018.03.030
|View full text |Cite
|
Sign up to set email alerts
|

The physiological effects of transcranial electrical stimulation do not apply to parameters commonly used in studies of cognitive neuromodulation

Abstract: Transcranial direct current stimulation (tDCS) and transcranial random noise stimulation (tRNS) have been claimed to produce many remarkable enhancements in perception, cognition, learning and numerous clinical conditions. The physiological basis of the claims for tDCS rests on the finding that 1 mA of unilateral anodal stimulation increases cortical excitation and 1 mA of cathodal produces inhibition. Here we show that these classic excitatory and inhibitory effects do not hold for the bilateral stimulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 37 publications
2
42
0
1
Order By: Relevance
“…A final further consideration of our results is the choice of stimulation parameters used. While prior work has shown that the use of bilateral electrode montages for tRNS stimulation can modulate performance in cognitive and perceptual domains (e.g., Cappelletti et al, 2013 ; Snowball et al, 2013 ; Joos et al, 2015 ; Romanska et al, 2015 ; Campana et al, 2016 ; Popescu et al, 2016 ; van der Groen and Wenderoth, 2016 ; van Koningsbruggen et al, 2016 ; Looi et al, 2017 ; Penton et al, 2017 ; Yang and Banissy, 2017 ), recent work using bilateral electrode montages for tRNS to stimulate the motor system has found that this approach does not induce the classical excitatory effects of unilateral tRNS ( Parkin et al, 2018 ). This is similar to studies of transcranial direct current stimulation (tDCS: a more commonly used transcranial electrical brain stimulation technique), where many studies find behavioral differences using bilateral electrode montages, but work using bilateral tDCS montages to modulate activity in the motor system has found mixed results on motor cortex excitability changes (e.g., Nitsche and Paulus, 2000 ; Mordillo-Mateos et al, 2012 ; Sehm et al, 2013 ; Parkin et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A final further consideration of our results is the choice of stimulation parameters used. While prior work has shown that the use of bilateral electrode montages for tRNS stimulation can modulate performance in cognitive and perceptual domains (e.g., Cappelletti et al, 2013 ; Snowball et al, 2013 ; Joos et al, 2015 ; Romanska et al, 2015 ; Campana et al, 2016 ; Popescu et al, 2016 ; van der Groen and Wenderoth, 2016 ; van Koningsbruggen et al, 2016 ; Looi et al, 2017 ; Penton et al, 2017 ; Yang and Banissy, 2017 ), recent work using bilateral electrode montages for tRNS to stimulate the motor system has found that this approach does not induce the classical excitatory effects of unilateral tRNS ( Parkin et al, 2018 ). This is similar to studies of transcranial direct current stimulation (tDCS: a more commonly used transcranial electrical brain stimulation technique), where many studies find behavioral differences using bilateral electrode montages, but work using bilateral tDCS montages to modulate activity in the motor system has found mixed results on motor cortex excitability changes (e.g., Nitsche and Paulus, 2000 ; Mordillo-Mateos et al, 2012 ; Sehm et al, 2013 ; Parkin et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…While prior work has shown that the use of bilateral electrode montages for tRNS stimulation can modulate performance in cognitive and perceptual domains (e.g., Cappelletti et al, 2013 ; Snowball et al, 2013 ; Joos et al, 2015 ; Romanska et al, 2015 ; Campana et al, 2016 ; Popescu et al, 2016 ; van der Groen and Wenderoth, 2016 ; van Koningsbruggen et al, 2016 ; Looi et al, 2017 ; Penton et al, 2017 ; Yang and Banissy, 2017 ), recent work using bilateral electrode montages for tRNS to stimulate the motor system has found that this approach does not induce the classical excitatory effects of unilateral tRNS ( Parkin et al, 2018 ). This is similar to studies of transcranial direct current stimulation (tDCS: a more commonly used transcranial electrical brain stimulation technique), where many studies find behavioral differences using bilateral electrode montages, but work using bilateral tDCS montages to modulate activity in the motor system has found mixed results on motor cortex excitability changes (e.g., Nitsche and Paulus, 2000 ; Mordillo-Mateos et al, 2012 ; Sehm et al, 2013 ; Parkin et al, 2018 ). Similarly, while many studies show behavioral effects of tRNS using durations of stimulation for 10 min or more (e.g., Cappelletti et al, 2013 ; Snowball et al, 2013 ; Joos et al, 2015 ; Romanska et al, 2015 ; Campana et al, 2016 ; Popescu et al, 2016 ; van Koningsbruggen et al, 2016 ; van der Groen and Wenderoth, 2016 ; Looi et al, 2017 ; Penton et al, 2017 ; Yang and Banissy, 2017 ), recent work in the motor system suggest that excitatory effects of tRNS may not be present at longer durations of stimulation (comparing 10 to 20 min stimulation parameters; Parkin et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Слабкий ПС підвищує ефективність когнітивних функцій, зокрема пам'яті [1][2][3][4]. Транскраніальна та трансвертебральна «мікрополяризація» виявляє протекторний ефект при використанні у гострий період уражень ЦНС та у разі віддалених наслідків при патологічних станах різного ґенезу [9,10]. Спрямований на зони ушкодження вплив слабкого ПС сприяє підтримці клітинного і тканинного гомеостазу [6,[11][12][13].…”
Section: вступunclassified
“…is assumed that higher current densities are required to activate the representation of the leg in 74 the motor cortex, or that increased 'dose' will result in greater ergogenic effects though this is 75 unlikely (see Parkin et al, 2015Parkin et al, , 2019. The relationship between current intensity and changes 76 in corticospinal excitability is non-linear, and stimulation intensities over 1 mA may limit or even 77 reverse the canonical polarity-dependent changes to the MEP (Batsikadze et al, 2013;Wiethoff 78 et al, 2014).…”
mentioning
confidence: 99%